REMAJA HEBAT : REMAJA DAN KEMAHIRAN DIRI UNTUK CEMERLANG. - Kamarul Azmi Jasmi, editor; Ahmad Kilani Mohamed, contributor; Ahmad Marzuki Mohamed, 1980-, contributor; Azmi Shah Suratman, 1959-, contributor; Juliana Ahmad Jamil, 1985-, contributor; Kamarul Azmi Jasmi, contributor; Mohd. Abbas Abd. Latiff, contributor; Mohd. Ismail Mustari, 1967-, contributor; Mohd. Nasir Ripin, contributor; Muhammad Syahmi Sulaiman, 1985-, contributor; Nora Ashikin A. Razak, contributor; Nur Naqibah Baharudin, contributor; et al. (Johor Bahru, Johor : PENERBIT UTM PRESS, 2017)
Includes bibliographical references and index